Outcome of the first 200 patients with prostate cancer treated with MRI-Linac at Assuta MC - Gelbart Pridan, Or; Ben David, Merav Akiva; Zalmanov, Svetlana; Lipski, Yoav; Grinberg, Vladislav; Levin, Daphne; Apter, Sara; Guindi, Michal; Epstein, Dan; Radus, Roman; Arsenault, Orit; Hod, Keren; et al. (Frontiers in Oncology, 2023)
Background: We present our experience with MR-guided stereotactic body radiotherapy (SBRT) for 200 consecutive prostate cancer patients with minimum 3 months follow-up. Methods: Treatment planning included fusion of the 0.35 Tesla planning MRI with multiparametric MRI and PET-PSMA for Group Grade (GG) 2 or higher and contour review with an expert MRI radiologist. No fiducials or rectal spacers were used. Prescription dose was 36.25Gy in 5 fractions over 2 weeks to the entire prostate with 3mm margins. Daily plan was adapted if tumor and OAR doses differed significantly from the original plan. The prostate was monitored during treatment which was automatically interrupted if the target moved out of the PTV range. Results: Mean age was 72 years. Clinical stage was T1c-85.5%, T2-13%, T3-1.5%. 20% were GG1, 50% GG2, 14.5% GG3, 13% GG4 and 1 patient GG5. PSA ranged from 1-77 (median 6.2). Median prostate volume was 57cc, and 888/1000 (88%) fractions required plan adaptation. The most common acute GU toxicity was Grade I-31%, dysuria and acute GI toxicity were rare. 3 patients required temporary catheterization. Prostate size of over 100cc was associated with acute fatigue, urinary hesitance and catheter insertion. PSA decreased in 99% of patients and one patient had regional recurrence. Conclusions: MR guided prostate SBRT shows low acute toxicity and excellent short-term outcomes. Real-time MR imaging ensures accurate positioning and SBRT delivery.